Mariotte bottle in a centrifuge: a device for constant water table level. Issue 1 (March 2002) - Thorel, Luc; Favraud, Claude; Garnier, Jacques
Abstract : In centrifuge geotechnical modelling, it is often needed to keep constant water table inside the soil sample. When the fluid is expected to move during the experiment (e.g. capillary rise, drainage, …), a special technique should be used. In lieu of the usual overflow pipe with a permanent flow supply, the Mariotte Bottle, a simple closed system, has been developed. The principles and limitations of this new device are described, and an example is given in the field of geo-environmental centrifuge modelling.